Implementasi Web Service Dalam Tracking Pengiriman Barang Dengan Metode Restfull Api Pada PT Bona Nusantara Raya Sakti - Romadoni, Achmad; Surapati, Untung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the context of modern business, logistics management and goods tracking are crucial to ensure efficiency and accuracy in the supply chain. However, PT Bona Nusantara Raya Sakti, a company that has been operating for 20 years, does not have a dedicated application system for tracking goods. This poses a challenge in effectively monitoring and managing the movement of goods from source to final destination. This research aims to design and develop a webbased freight tracking application using the RESTful API method for PT Bona Nusantara Raya Sakti. The main objective of this research is to improve the efficiency of the logistics process and facilitate the tracking of goods, thereby reducing the risk of loss and improving service quality. Development starts from indepth needs analysis, implementation using RESTful API technology, testing to ensure application reliability and security, to periodic system maintenance. The results of this research are expected to make a positive contribution in improving the operational efficiency of PT Bona Nusantara Raya Sakti, as well as providing the right solution in logistics management and overall tracking of goods delivery. With this application, it is expected that the company can optimize its logistics process and provide better service to customers.